Ski7p G protein interacts with the exosome and the Ski complex for 3′-to-5′ mRNA decay in yeast - Araki, Yasuhiro (Oxford University Press, 2001)
Two cytoplasmic mRNA-decay pathways have been characterized in yeast, and both are initiated by shortening of the 3′-poly(A) tail. In the major 5′-to-3′ decay pathway, the deadenylation triggers removal of the 5′-cap, exposing the transcript body for 5′-to-3′ degradation. An alternative 3′-to-5′ decay pathway also follows the deadenylation and requires two multi-complexes: the exosome containing various 3′-exonucleases and the Ski complex consisting of the RNA helicase Ski2p, Ski3p and Ski8p. In addition, Ski7p, which has an N-terminal domain and a C-terminal elongation factor 1α-like GTP-binding domain, is involved in the 3′-to-5′ decay. However, physical interaction between the exosome and the Ski complex, together with the function of Ski7p, has remained unknown. Here we report that the N domain of Ski7p is required and sufficient for the 3′-to-5′ decay. Furthermore, the exosome and the Ski complex interact with the different regions of Ski7p N domain, and both interactions are required for the 3′-to-5′ decay. Thus, Ski7p G protein appears to function as a signal-coupling factor between the two multi-complexes operating in the 3′-to-5′ mRNA-decay pathway.